RGB camera-based simultaneous measurements of percutaneous arterial oxygen saturation, tissue oxygen saturation, pulse rate, and respiratory rate - Nishidate, Izumi; Yasui, Riku; Nagao, Nodoka; Suzuki, Haruta; Takara, Yohei; Ohashi, Kaoru; Ando, Fuminori; Noro, Naoki; Kokubo, Yasuaki (Frontiers in Physiology, 2022)
We propose a method to perform simultaneous measurements of percutaneous arterial oxygen saturation (SpO2), tissue oxygen saturation (StO2), pulse rate (PR) and respiratory rate (RR) in real time, using a digital red-green-blue (RGB) camera. Concentrations of oxygenated hemoglobin (CHbO), deoxygenated hemoglobin (CHbR), and total hemoglobin (CHbT), and StO2 were estimated from videos of the human face using a method based on a tissue-like light transport model of the skin. The photoplethysmogram (PPG) signals are extracted from the temporal fluctuations in CHbO, CHbR, and CHbT using a finite impulse response (FIR) filter (low and high cut-off frequencies of 0.7 and 3 Hz, respectively). PR is calculated from the PPG signal for CHbT. The ratio of pulse wave amplitude for CHbO and that for CHbR are associated to the reference value of SpO2 measured by a commercially available pulse oximeter, which provide an empirical formula to estimate SpO2 from videos. The respiration-dependent oscillation in CHbT was extracted from another FIR filter (low and high cut-off frequencies of 0.05 and 0.5 Hz, respectively) and used to calculate RR. In vivo experiments with human volunteers while varying the fraction of inspired oxygen were performed to evaluate comparability of the proposed method with the commercially available devices. Bland-Altman analysis showed that the mean bias for PR, RR, SpO2, and StO2 were -1.4 [bpm], -1.2[rpm], 0.5 [%], and -3.0 [%], respectively. The precisions for PR, RR, SpO2, and StO2 were ±3.1 [bpm], ±3.5 [rpm], ±4.3 [%], and ±4.8 [%], respectively. The resulting precision and RMSE for StO2 was pretty close to the clinical accuracy requirement. The accuracy of RR is considered little less accurate than clinical requirements. This is the first demonstration of a low-cost RGB camera-based method for contactless simultaneous measurements of heart rate, percutaneous arterial oxygen saturation, and tissue oxygen saturation in real time.